Three Drosophila mutations that block associative learning also affect habituation and sensitization. - Duerr, J S (1982)
Drosophila melanogaster has been cultured with shock to avoid various odors. Mutants that failed to learn this task have been isolated. Here we report tests on these mutants for more elementary types of behavioral plasticity--habituation and sensitization of a reflex. Fruit flies have taste receptors on their feet. When a starved, water-satiated fly has sucrose applied to one foot, it usually responds by extending its proboscis. In normal flies this feeding reflex shows habituation: application of sugar to one foot depresses responsiveness through the contralateral leg for at least 10 min. The reflex also shows brief sensitization application of concentrated sucrose solution to the proboscis increases subsequent responsiveness to tarsal stimulation for 2-5 min. In three associative learning mutants , the proboscis-extension reflex is present with a normal threshold but behavioral modulation of the response is altered. The dunce, turnip, and rutabaga mutants all habituate less than normal flies. In addition, sensitization wanes unusually rapidly in dunce and rutabaga flies, lasting less than a minute in the case of dunce.